2021
DOI: 10.1002/fuce.202100019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the crystallographic expansion of GSC and LSC porous electrodes

Abstract: Characteristics of the porous Gd 0.15 Sr 0.85 CoO 3−δ and La 0.6 Sr 0.4 CoO 3−δ cathodes were compared using the data measured at different electrode potentials and oxygen partial pressures. The electrochemical high-temperature in situ XRD (HT-XRD) method combined with electrochemical impedance spectroscopy has been used. The response of the crystallographic parameters and impedance values on the changes of electrode potential has been discussed. Reversible changes of the lattice parameters for both cathodes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…and the B-site (such as Fe, Ni, etc.) of SrTiO 3 -based compounds offers the potential to enhance catalytic activity, electrical conductivity, and chemical stability of these materials. , It has been reported that among perovskite structures with lanthanoids (Ln), like La, Pr, Nd, Sm, and Gd as dopants in the A-site of Ln x Sr 1– x Co y Fe 1– y O 3−δ , the composition with Nd demonstrates the best electrical conductivity and very good catalytic activity for oxygen reduction . Additionally, Tamimi et al observed that materials incorporating Nd exhibited lower electrode impedance compared to those with La in Ln 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (Ln = La, Pr, Nd).…”
Section: Introductionmentioning
confidence: 99%
“…and the B-site (such as Fe, Ni, etc.) of SrTiO 3 -based compounds offers the potential to enhance catalytic activity, electrical conductivity, and chemical stability of these materials. , It has been reported that among perovskite structures with lanthanoids (Ln), like La, Pr, Nd, Sm, and Gd as dopants in the A-site of Ln x Sr 1– x Co y Fe 1– y O 3−δ , the composition with Nd demonstrates the best electrical conductivity and very good catalytic activity for oxygen reduction . Additionally, Tamimi et al observed that materials incorporating Nd exhibited lower electrode impedance compared to those with La in Ln 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (Ln = La, Pr, Nd).…”
Section: Introductionmentioning
confidence: 99%